QUARANTINE IS NOT A REASON TO NEGLECT EDUCATION AND HOW ONLINE EDUCATION WILL CHANGE DURING A PANDEMIC - Mavlyanova Tamilla Baxrilloevna (International Journal of Innovations in Engineering Research and Technology, 2021)
Before writing this article, for a long time I tried to analyze all those events that have overtook us in recent months and weeks. We are all aware that humanity on Earth is facing a coronavirus pandemic. The coronavirus pandemic has made adjustments to all areas of our lives, especially in the field of education. The heads of states were forced to announce quarantine to ensure the safety of all citizens. But quarantine is not a reason not to study and abandon the educational process. On the contrary, this is a great chance to learn even more and start doing better. Currently, students and teachers are forced to optimize their work through the Internet. With all the negativity from the consequences of the epidemic, being at remote work distance learning or in self-isolation mode, we must not forget about the positive feelings that need to be awakened and cultivated in ourselves during the era of the “New Decameron”, the coronavirus pandemic, such as: humanism, empathy, sympathy.